A kinematic analysis of acute and longitudinal adaptions to resisted sprinting - Hansen, K. (Auckland University of Technology, 2002)
The phase of greatest acceleration (0-30 metres) during sprinting is thought to be critical for success in many sporting situations. Methods for improving acceleration phase performance are therefore an important area of study for conditioners and sports scientists. Typically a variety of resistance training techniques are used to improve strength and power of the lower limb musculature that is important to sprinting performance. One such technique is resisted sprinting which involves the use of apparatus such as weighted vests and sleds to provide movement specific overload to athletes. The purpose of this thesis was primarily, to compare sprint times, step variables and joint kinematics when sprinting with a vest loaded at 15% and 20% of the athlete's body mass and towing a sled with 15% and 20% of body mass. A secondary aim was to examine the effect of a six-week training program utilising resisted sprinting on acceleration phase performance in three athletes.In the first study, 20 semi-elite subjects performed five 30-metre sprints: one unloaded sprint, two sled sprints loaded at 15% of their body mass and 20% of their body mass, and two vest sprints with the same loads relative to body mass. Each sprint was videoed in the sagittal plane at five, 15 and 25 metres from the start of the 30-metre sprint and times were recorded at 10 and 30-metres using timing lights. Video data were digitised and the following step variables were calculated: step length, step frequency, stance phase duration and swing phase duration. Stance phase angles of the trunk, thigh, knee and ankle were also calculated. Step length, step frequency and swing phase duration during vest and sled sprinting were found to decrease significantly (P<0.05) when compared to unloaded sprinting values. Stance phase duration during vest and sled sprinting increased compared to unloaded sprinting values (P<0.05). Additionally, sled towing displayed significantly greater (P<0.05) trunk flexion at foot strike and toe-off, and significantly greater (P<0.05) knee flexion at foot strike than both the unloaded and vest sprinting conditions. Sled towing also induced significantly greater thigh extension at toe-off compared to the vest conditions (P<0.05). Thus the addition of load to the athlete via vest sprinting and sled towing may influence performance in different ways, and hence the objective of the athlete should be considered when choosing which of these techniques to use.In the second study, a single subject research design was utilised to assess whether sled towing and vest sprinting resulted in changes in performance over a six-week period of training. In this study, three subjects trained twice a week for six weeks using resisted sprinting. Subjects were randomly assigned to sled training, vest training or combination training (one training session a week with each apparatus). Subjects were tested at baseline, after three weeks of training and after six weeks of training for 10 and 30-metre sprint times and selected step variables (step length, step frequency and stance phase duration). Data analysis involved both visual analysis of graphed data and statistical analysis using the two standard deviation band method. The combination training subject improved performance over both 10 and 30 metres. Step variable data were inconclusive regarding the mechanisms behind these improvements. Neither sled towing nor vest sprinting resulted in significant improvements in performance. The results indicated that the use of both training apparatus in unison may be required in order to improve performance during the acceleration phase of sprinting.